THE EFFECT OF DUOLINGO APPLICATION ON VOCABULARY MASTERY - Megasari Br Siregar; Fadly Azhar; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: In this modern era, technology has the potential to make life easier and more efficient, especially in education. Where technology is able to solve learning problems. Teachers are encouraged to use technology as a tool or medium to boost student excitement for learning English, especially vocabulary, because there are so many students who are not interested in studying. The purpose of this study is to ascertain whether the Duolingo app affects students' vocabulary mastery. This research was carried out using a quasi-experimental design. There were 68 students in the sample for this study. 34 students made up class XI IPA 4 (the experiment class), and 34 students made up class XI IPA 3 (the control class). This study was conducted in SMA Negeri 1 Tapung Hulu. The post-test was administered following the use of the treatment for 4 meetings while utilizing the Duolingo app as a supplemental tool for learning English. The data was examined using the t-test. The t-count value was 12.57 and the t-table value was 1.99 according to the study's findings. This demonstrates the acceptance of the alternative hypothesis (Ha) that the Duolingo application has a significant impact on the vocabulary mastery of SMA Negeri 1 Tapung Hulu students in the 11th grade.Key Words: Vocabulary Mastery, Duolingo Application, Senior High School Students.